Effect of Germination on the Nutritional and Protein Profile of Australian Sweet Lupin (Lupinus angustifolius L.) - Rumiyati, R.; James, Anthony; Jayasena, Vijay (Scientific Research Publishing Inc, 2012)
Australian Sweet Lupin (ASL) has a nutritional profile ideally suited for human consumption with high protein and fibre, but low starch and fat content. The nutritional and protein profile of germinated ASL may be better than ungerminated ASL and these improvements would provide further benefits in its use as an ingredient in food applications. In this study the nutritional components such as protein, crude fibre, fat and protein profile of germinated ASL flour following germination at 25°C and 90% - 95% relative humidity for 9 days were determined. The changes in the pattern of ASL protein during germination were analysed using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). Germination significantly increased crude fibre contents by 450% (db), total protein contents by 38% (db) and decreased the fat content by 70% (db) at day 9 of germination. Electrophoretic analysis of the protein fractions revealed that during germination up to 9 days, some of the high molecular weight proteins disappeared. Germination represents a means to further improve the nutritional profile of the germinated ASL flour with an increased fibre and protein, but lower fat content.